Systemic challenges and opportunities of Franco-German development cooperation - Lennart Kaplan (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
France and Germany face common issues in global development policy, including climate change, migration and security. At the same time, their aid is spread across similar countries and sectors. Based on a quantitative overlap measure, the study reveals that the Franco-German overlap of aid allocation is more than four times as high as for the average donor. If France and Germany can bridge their divisions, the high overlap provides a momentum to take a leading role for international donor coordination. This is key in view of the opportunities and challenges of 2020 and beyond, including the German presidency of the Council of the European Union (EU), climate change as well as the recent Covid-19 pandemic. Against this background, this study explores the systemic challenges and opportunities for a stronger Franco-German coordination in the framework of four country case studies, where development cooperation of both donors strongly overlaps. Evidence from Benin, Cameroon, India and Morocco reveals that the complex development systems of the two donors impose differing time horizons and standards of procedure. Moreover, geo-political priorities complicate consensus building. The case studies stress that sustainable Franco-German cooperation only works based on a regular exchange both on the political and operational level. In this regard, the long-lasting partnership between the French and German development banks, Agence Française de Développment (AFD) and Kreditanstalt für Wiederaufbau Entwicklungsbank (KfW), illustrates how mutual understanding and careful reconciliation of approaches can facilitate cooperation. Combining capacities, France and Germany finance large-scale projects to achieve sustainable development and, this way, crowd-in resources by other development actors from the EU and beyond. Although reconciling standards in technical cooperation is more challenging, the French and German agencies, Gesellschaft für Internationale Zusammenarbeit and Expertise France, are currently negotiating similar measures.
Keywords: 330; coordination; fragmentation; ODA overlap; French-German cooperation; European development cooperation; India; Cameroon; Benin; Morocco